The effect of using simpatika to improve supervision of pak teacher’s performance at the religion ministry of ambon city - Margaretha Louisa Mahakena (12 Waiheru, 2022)
Simpatika application is a system that is used to input the Christian teachers' data who are in the scope of the ministry of religion. Empirically, this system inputs the teacher's data all at once to supervise teachers' activity in their school. Furthermore, this simpatika aims to supervise every Christian teacher's activity to teach in their school, what are the teaching hours and subject of study which their teaching with according to the diploma they have. Other than that, supervise and assess the performance of Christian teachers. In the ministry of the religion of Ambon city, the number of Christian teachers and education staff is 448 people, with details of 180 active PTK and 268 non-active PTK. Therefore, required a professional operator so they can implement a job well.